PENGARUH MOTIVASI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN - wijaya, darma (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2017)
The analysis showed that there was a significant positive effect of Motivation and the Lifestyle toward Buying Decision . This suggests that higher levels of motivation and Lifestyle in the mind of the consumer laptop users will increase also Buying Decision-owned .